Walking through night markets: a study on experiencing everyday urban culture - Zakariya, Khalilah (2010)
Temporary markets can be considered as everyday spaces in the city. There is something unpretentious about walking through a night market or a weekly bazaar, and yet, there is also something spectacular and festive about experiencing these informal, temporary event spaces. They are often a common feature in guide books for cities, enticing visitors to engage and experience the local life. Temporary markets may look similar at a glance or through photographs, but a conscious experience through them generates a richer and more complex understanding of their similarities and differences, how they operate as part of the city, and how places in the city are interconnected. This paper presents a collection of walking experiences through different temporary markets in Kuala Lumpur, Malaysia, ranging from less formal to more formal ones, while exploring their qualities and senses. The study employs an ethnographic approach through my own personal walking experience, engaging in the experiences of others, observations and conversations with vendors and visitors, mapping, and photo-documentation. The discussion from the findings challenges us to rethink the complexities of temporary markets as both ordinary and extra-ordinary spaces, and shares how we can engage with a rich phenomenon.